Functional Amino Acids and Autophagy: Diverse Signal Transduction and Application - Chunchen Liu (MDPI AG, 2021)
Functional amino acids provide great potential for treating autophagy-related diseases by regulating autophagy. The purpose of the autophagy process is to remove unwanted cellular contents and to recycle nutrients, which is controlled by many factors. Disordered autophagy has been reported to be associated with various diseases, such as cancer, neurodegeneration, aging, and obesity. Autophagy cannot be directly controlled and dynamic amino acid levels are sufficient to regulate autophagy. To date, arginine, leucine, glutamine, and methionine are widely reported functional amino acids that regulate autophagy. As a signal relay station, mammalian target of rapamycin complex 1 (mTORC1) turns various amino acid signals into autophagy signaling pathways for functional amino acids. Deficiency or supplementation of functional amino acids can immediately regulate autophagy and is associated with autophagy-related disease. This review summarizes the mechanisms currently involved in autophagy and amino acid sensing, diverse signal transduction among functional amino acids and autophagy, and the therapeutic appeal of amino acids to autophagy-related diseases. We aim to provide a comprehensive overview of the mechanisms of amino acid regulation of autophagy and the role of functional amino acids in clinical autophagy-related diseases and to further convert these mechanisms into feasible therapeutic applications.